2019
DOI: 10.3389/fgene.2019.00073
|View full text |Cite
|
Sign up to set email alerts
|

Natural Selection Equally Supports the Human Tendencies in Subordination and Domination: A Genome-Wide Study With in silico Confirmation and in vivo Validation in Mice

Abstract: We proposed the following heuristic decision-making rule: “IF {an excess of a protein relating to the nervous system is an experimentally known physiological marker of low pain sensitivity, fast postinjury recovery, or aggressive, risk/novelty-seeking, anesthetic-like, or similar agonistic-intolerant behavior} AND IF {a single nucleotide polymorphism (SNP) causes overexpression of the gene encoding this protein} THEN {this SNP can be a SNP marker of the tendency in dominance} WHILE {underexpression corresponds… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 90 publications
(159 reference statements)
1
12
0
2
Order By: Relevance
“…table S presents the gene expression levels revealed by qPCR and their statistical analysis performed in this work (see Supplementary file "Supplementary experiment"). (Chadaeva et al, 2017), which was already proved on F1 hybrid mice (Chadaeva et al, 2019), here we predicted and then demonstrated overexpression of Cacna2d3, Gad2, Gria2, Mapk1, Nos1, Pomc, and Syn1 in the hypothalamus, but not PAG, of aggressive male rats versus domesticated ones. This result means predictability of this phenomenon only within the framework of the basic principle of breeding genetics taken into account together with the natural selection against underexpression of aggressiveness-related genes rather than exceptional importance of these genes for aggressive behavior.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…table S presents the gene expression levels revealed by qPCR and their statistical analysis performed in this work (see Supplementary file "Supplementary experiment"). (Chadaeva et al, 2017), which was already proved on F1 hybrid mice (Chadaeva et al, 2019), here we predicted and then demonstrated overexpression of Cacna2d3, Gad2, Gria2, Mapk1, Nos1, Pomc, and Syn1 in the hypothalamus, but not PAG, of aggressive male rats versus domesticated ones. This result means predictability of this phenomenon only within the framework of the basic principle of breeding genetics taken into account together with the natural selection against underexpression of aggressiveness-related genes rather than exceptional importance of these genes for aggressive behavior.…”
Section: Discussionsupporting
confidence: 80%
“…Using it, we predicted candidate SNP markers of human aggressiveness (Chadaeva et al, 2016) and natural selection against underexpression of human aggressiveness-related genes (Chadaeva et al, 2017). Recently, we proved this natural selection pattern using F1 hybrid male mice as an animal model of human heredity (Chadaeva et al, 2019). Simultaneously, this natural selection equally supports two opposing traits in humans (i.e., dominance and subordination) as if self-domestication could have happened with its characteristic disruptive natural selection as Belyaev (1979) discovered in wild and domesticated foxes half a century ago.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, we applied this software to predict candidate SNP markers of resistance to anticancer therapy [47] [53], and domination and subordination within a social hierarchy [54]. In these works of ours, we studied only SNPs located within 70 bp proximal promoter regions in front of transcription start sites of the human genes because TBP-sites are necessary here [21].…”
Section: Introductionmentioning
confidence: 99%
“…Our recent study on this topic is about 34 candidate SNP markers of atherosclerosis [55] that are located around the clinical SNP markers in TBP-sites of 17 human gene promoters. These clinical SNP markers seem to be subject to neutral drift as genetic loads, according to the statistical estimates from our previous works [49][50][51]54] within the framework of Kimura's theory [24] and Haldane's dilemma [25] using a previous dbSNP build (No. 147 dated 2016) [12].…”
Section: Introductionmentioning
confidence: 99%
“…На этой основе мы создали Webсервис SNP_TATA_Comparator (Ponomaren ko et al, 2015) для применения указанного уравнения свя зывания ТВР с ДНК в процессе анализа референсного генома че ловека (Telenti et al, 2016). С помощью SNP_TATA_Com pa ra tor ранее уже был сделан прогноз кандидатных SNP маркеров агрессивности, женского репродуктивного по тенциала, предрасположенности к социальному подчи нению и доминированию, а также ожирения, нарушений циркадного ритма, аутоиммунных заболеваний и болезни Альцгеймера (Arkova et al, 2015;Chadaeva et al, 2016Chadaeva et al, , 2018Chadaeva et al, , 2019Ponomarenko P. et al, , 2017. В настоящей работе мы представля ем обновление SNP_TATA_Ztester этого Webсервиса (Ponomarenko et al, 2015) и результаты его применения к исследованию РА в качестве продолжения серии наших биоинформатических прогнозов.…”
Section: Introductionunclassified